PERAN BIDANG REHABILITAS DINAS SOSIAL DALAM PENANGGULANGAN FAKIR MISKIN DI KABUPATEN SUMEDANG - Abdurrahmat Fathoni; Dadang Priatna; Relinda Saskia (LPPM UNSAP & FISIP UNSAP, 2023)
Role is a dynamic aspect in the form of actions or behaviors that carry out rights and obligations in accordance with their position. The role of the Social Service in its implementation turns out that there are still many that are not running because one of the factors that results in the high number of poverty is the character of some residents of Sumedang regency who are not good, namely their recognition as poor people, especially when there are programs from the government, so it is not uncommon for poor people who need help not to get a share in the program. This study aims to examine the role of social services in handling the poor in Sumedang district. This research uses a qualitative approach. The number of informants in the study was 4 people. Data collection techniques are carried out with interviews and documentation. Meanwhile, the data validation technique that researchers use is triangulation. The selection of informants is based on that the informant has knowledge, and information regarding the subject matter carefully. The results showed that the role of the Social Service in handling the poor in Sumedang district is seen from the aspect of the government as a regulator in the government's poor handling program that still does not play an active role in improving the economy so that poverty can be explained and resolved. The government as a dynamicator, the Sumedang Regency government in improving the economic quality of the community so that government programs related to handling the poor in Sumedang Regency are still not running well. The government as a facilitator, social service provides good services and facilities, especially in the implementation of poverty reduction programs, but the government as a facilitator has not played an active role in building conditions that are conducive to the implementation of regional development.